Nothing left to lose? Poverty and social exclusion in comparison. Empirical evidence on Germany - Petra Böhnke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The assumption that today.s society is polarised, is a very popular one in the current public and scientific debate. Access to the labour market is referred to as the main characteristic, which decides whether someone is .inside. or .outside.. Lots of theoretical and conceptual efforts have been undertaken to establish dimensions and characteristics of social exclusion, addressing processes of denied participation . socially, economically, politically or culturally. Nevertheless, poverty and social exclusion as two descriptions of severe social inequality have often been mixed up, and hypothesis about their interrelation and characteristics have hardly been tested empirically. Is poverty the first stage on the way .out of society., or are there considerable differences between the risk of becoming poor or socially excluded? In this contribution I propose the conceptualization and operationalization of social exclusion tendencies on the basis of the German Welfare Survey 1998. First of all, the multidimensionality of social exclusion is analysed to gain an insight into its structure. Of particular interest is the question how cumulative social disadvantages show their effect on perceived social exclusion in the view of the respondents. Furthermore, I concentrate on the relationship between poverty and social exclusion and compare the determinants of becoming poor and socially excluded. – – Die Annahme, daß sich die Gesellschaft polarisiere, ist gegenwärtig in der öffentlichen Diskussion und politischen Debatte sehr populär. Der Zugang zum Arbeitsmarkt, so eine Hauptthese der deutschen Debatte um soziale Ausgrenzung, bestimme wesentlich darüber, ob jemand .drinnen. oder .draußen. sei. Soziale Ausgrenzung zielt auf die nicht mehr gewährleistete Teilhabe in vielfältiger Hinsicht: sozial, ökonomisch, politisch und kulturell. Armut und soziale Ausgrenzung als zwei Beschreibungen extremer sozialer Ungleichheit werden dabei oft vermischt, ohne dass Hypothesen über ihre Verbindung und ihre spezifischen Charakteristika empirisch überprüft worden wären. Führt existentieller Geldmangel unabdingbar zu einer Gefährdung sozialer Integration? Oder lassen sich wesentliche Unterschiede zwischen dem Armuts- und dem Ausgrenzungsrisiko ausmachen? In diesem Beitrag wird mit Hilfe von Daten des Wohlfahrtssurveys 1998 eine Konzeptionalisierung und Operationalisierung sozialer Ausgrenzungstendenzen vorgeschlagen. Von Interesse ist zum einen die Struktur und das Ausmaß kumulativer sozialer Benachteiligung. Darüber hinaus wird analysiert, ob prekäre Lebenslagen mit subjektivem Ausgrenzungsempfinden einhergehen und welche Voraussetzungen sozialstruktureller Art gegeben sein müssen, um von Armut oder sozialer Ausgrenzung bedroht zu sein.
Keywords: 300; Armut; Soziale Isolation; Lebensstandard; Einkommensverteilung; Deutschland; Randgruppe